2008
DOI: 10.1002/pssc.200778719
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature grown compositionally graded InGaN films

Abstract: A new thin film growth technique known as energetic neutral atomic‐beam lithography/epitaxy (ENABLE) provides a large energetic N atom flux and eliminates the need for high substrate temperatures as compared to molecular beam epitaxy, making isothermal growth over the entire InGaN alloy composition range possible without phase separation. 500–800 nm thick compositionally graded InGaN films were grown by ENABLE at ∼450 °C with the following structure types: (1) with the Ga‐rich material on the surface and (2) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…The fraction of indium content in the InGaN layer is 0.25. The GaN is p þ doped while the InGaN is n þ doped to create effective carrier concentrations of 10 16 holes/cm 3 and 10 18 electrons/ cm 3 , respectively. Although Sentarus is capable of handling piezoelectric polarization internally, the developed model in the present structure cannot include strain and stress dependent polarization effects.…”
Section: Modeling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fraction of indium content in the InGaN layer is 0.25. The GaN is p þ doped while the InGaN is n þ doped to create effective carrier concentrations of 10 16 holes/cm 3 and 10 18 electrons/ cm 3 , respectively. Although Sentarus is capable of handling piezoelectric polarization internally, the developed model in the present structure cannot include strain and stress dependent polarization effects.…”
Section: Modeling Methodsmentioning
confidence: 99%
“…Details on the ENABLE growth conditions have been reported previously. [15][16][17] Films grown by this technique tend to be inherently nitrogen polar. Base pressure for the growth chamber were $10 À10 Torr.…”
Section: Experiments Methodsmentioning
confidence: 99%
“…In both cases, isothermal growth at 500 °C made possible using ENABLE resulted in graded InGaN films that showed physical and optical characteristics consistent with good film quality, uniform and smooth grading of the film composition, and interesting optical properties. Preliminary details have been reported elsewhere [10]. Interestingly, PL data for both grading structures indicates that carrier recombination is strongly biased towards the lowest bandgap layers of the film structures.…”
mentioning
confidence: 88%
“…It can enhance the photogenerated carriers to tunnel through the energy barrier and result in a higher solar cell efficiency. The graded design is technologically feasible, as it has been shown that graded In y Ga 1Ày N layers can be grown over the entire composition range using the energetic neutral atom beam lithography and epitaxy (ENABLE) process [16]. The incorporation of linearly compositional graded In y Ga 1Ày N layer into device allows the production of efficient high indium content solar cells.…”
Section: Theorymentioning
confidence: 99%